The Influence of Non-Physical Environment and Performance Appraisal on the Performance Employee Through Work Stress as an Intervening Variable - Ayudini Samudri; Nurdjanah Hamid; Muhammad Yunus Amar (Hasanuddin Journal of Business Strategy, 2020)
This study aims to determine the direct and indirect effects of the non-physical environment and performance appraisal on the employee performance through work stress as an intervening variable. This research was conducted at the Makassar Branch of Bank Negara Indonesia using a questionnaire fo 85 respondents. The analysis technique using SPSS version 20. The results show that the non-physical environment has a significant effect on work stress. Interestingly, the performance appraisal has no significant effect on work stress, while the work stress has a significant effect on performance. The non-physical environment and the performance appraisal affects employee performance with work stress as an intervening variable.